The fallen tree: clarifying responsibilities for effective urban tree management - Kamal Azira, Anis Syafini; Aidzil Adzahar, Aliya Safiya; Jalil Husni, Hannah ‘Atikah; Mohd Azri, Dania Arisha; Mohd Khairi, Nur Ain Nadya; Ali, Adibah (Asian Scholars Network, 2025)
Malaysia has recently witnessed one unfortunate event involving a 144-year-old tree in Kuala Lumpur which have resulted in fatalities, injuries as well as damage to property. This tragic incident has sparked vigorous debates and significant public concern by raising questions about accountability throughout the country. This research paper aims to delve into the issues surrounding the incident to enhance understanding of it. Beginning with a detailed overview of the accident, this paper will meticulously examine the circumstances leading to the tree's collapse and the subsequent aftermath. It also analyses the involvement and duties of various stakeholders such as local authorities, property owners, and arborists, in ensuring public safety and reducing risks associated with unforeseen occurrences. Moreover, the concept of liability in this context is determined by analysing legal frameworks and judicial precedents. Through an awareness survey and comprehensive analysis of the legal provisions, this paper seeks to identify measures that can be taken to ensure that similar incidents can be prevented in the future. By shedding light on this issue, proactive tree management practices can be implemented, fostering a culture of shared responsibility for public safety.